A randomized, double-blind, placebo-controlled, dose-escalating phase I trial to evaluate safety and immunogenicity of a plant-produced, bivalent, recombinant norovirus-like particle vaccine - Leroux-Roels, Isabel; Maes, Cathy; Joye, Jasper; Jacobs, Bart; Jarczowski, Franziska; Diessner, André; Janssens, Yorick; Waerlop, Gwenn; Tamminen, Kirsi; Heinimäki, Suvi; Blazevic, Vesna; Leroux-Roels, Geert; et al. (Frontiers in Immunology, 2022)
Noroviruses (NoV) are the leading cause of epidemic acute gastroenteritis in humans worldwide and a safe and effective vaccine is needed. Here, a phase I, double-blind, placebo-controlled clinical trial was performed in 60 healthy adults,18 to 40 years old. Safety (primary objective) and immunogenicity (secondary and exploratory objectives) of a bivalent (GI.4 and GII.4), plant-produced, virus-like particle (VLP), NoV vaccine candidate formulation were investigated at two dose levels (50 µg + 50 µg and 150 µg + 150 µg) without adjuvant. Overall, 13 subjects (65.0%) in the 50 µg group, 16 subjects (80.0%) in the 150 µg group, and 14 subjects (70.0%) in the placebo group reported at least 1 solicited local or general symptom during the 7-day post-vaccination periods following each dose. Severe solicited adverse events (AEs) were rare (2 subjects in the 50 µg group). A total of 8 subjects (40.0%) in each group reported at least one unsolicited AE during the 28-day post-vaccination periods. Immunogenicity was assessed on days 1, 8, 29, 57, 183 and 365. All subjects were pre-exposed to norovirus as indicated by baseline levels of the different immunological parameters examined. Vaccine-specific humoral and cellular immune responses increased after the first dose but did not rise further after the second vaccination. Increased GI.4- and GII.4-specific IgG titers persisted until day 365. The vaccine elicited cross-reactive IgG antibodies against non-vaccine NoV VLPs, which was more pronounced for NoV strains of the same genotype as the GII.4 vaccine strain than for non-vaccine genotypes. Significant blocking anti-GI.4 and anti-GII.4 VLP titers were triggered in both dose groups. Lymphoproliferation assays revealed strong cell-mediated immune responses that persisted until day 365. In conclusion, both dose levels were safe and well-tolerated, and no higher incidence of AEs was observed in the higher dose group. The data show that a single dose of the vaccine formulated at 50 µg of each VLP is sufficient to reach a peak immune response after 8 to 28 days. The results of this Phase I study warrant further evaluation of the non-adjuvanted vaccine candidate.